Musical Genres - Horvat, Sara (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores the importance of the environment and pedagogical approaches in primary school for fostering acceptance of different musical genres. It emphasizes the role of the home and, especially, the school environment in shaping children's openness to diverse musical genres, as well as the significance of thoughtfully delivering musical content within the school setting. The principle of progression is highlighted as key to effectively introducing musical content, enabling pupils to gradually become acquainted with more complex rhythms and genres. Music impacts learning processes in various ways: classical music enhances concentration, pop music fosters emotional engagement, and ambient music stimulates creativity. This chapter also examines how musical content enriches the educational experience, promotes intercultural understanding, and contributes to the formation of values. It concludes by emphasizing the importance of integrating musical diversity into the school curriculum to support a holistic approach to learning.